HRCT quantitative analysis of airway remodeling and airway trapping in the small airway asthma phenotype and its correlation with pulmonary function. (2nd January 2023) - Lu, Dongzhu; Yu, Qing; Chen, Lichang; Liao, Qiannuan; Lan, Junkang; Chen, Shu-Bing; Wang, Cuilan; Zeng, Wenyi; Wu, Lingling; Fan, Chaofan; Lu, Peifeng; Yu, Huapeng
Abstract: Objectives: We aimed to explore whether large airway remodeling and small airway structural changes exist in subjects with small airway asthma phenotype and to evaluate the relationships between quantitative high-resolution computed tomography (qHRCT) parameters and lung function. Methods: We enrolled 15 subjects with small airway asthma phenotype and 18 healthy controls. The two groups were matched by age, sex and body square area (BSA) with propensity score matching (PSM). Pulmonary function and qHRCT parameters [wall thickness (WT), wall area (WA), lumen area (LA), wall area percentage (WA%) of the 4th–6th generations in the right upper lobe apical segmental bronchus (RB1), adjusted by BSA, WT/BSA, WA/BSA, and LA/BSA, relative volume change −860 HU to −950 HU (RVC−860 to −950 ) and the expiration to inspiration ratio of mean lung density (MLDE/I )) were compared between the groups. Correlation analysis was employed to assess the relationship between qHRCT parameters and pulmonary function. Results: The small airway asthma phenotype had significantly higher WA%, RVC−860 to −950 and MLDE/I and lower LA/BSA than the healthy control. Additionally, we found moderate to strong correlations between impulse oscillation (IOS) indices and WA6% and WT6/BSA. No significant correlation was found between bronchial parameters and air trapping parameters ( p  > 0.05). Conclusions: Combining physiological tests with imaging approaches can lead to better evaluation of small airway disfunction (SAD) in asthmatic patients. Additionally, despite nonexistent airflow obstruction in patients with small airway asthma phenotype, large airway remodeling and small airway structural changes may appear simultaneously in the early stage of disease.